Verbal and Non-verbal Signs of “Scream” Movie Posters - Ni Putu Mirah Handayani; Desak Putu Eka Pratiwi; I Gusti Ayu Vina Widiadnya Putri (Austronesian: Journal of Language Science & Literature, 2022)
This study aims to analyze the verbal and non-verbal signs and to figure out the meaning of verbal and non-verbal signs in Scream movie posters. An observation method was used to collect the data. The data were taken from two Scream movie posters downloaded from https://m.imdb.com. The method used is a qualitative approach. To analyze verbal and non-verbal signs, researchers used Saussure's semiotic theory, while to analyze the meaning, researchers used the theories of Barthes and Cerrato. As a result, the researchers found eight verbal and five non-verbal signs in these Scream movie posters. The creator's message is usually conveyed implicitly, requiring the viewers to interpret the meaning of the movie posters. The presence of both verbal and non-verbal signs in the movie poster serves to highlight the creator's message to the audience. Furthermore, a movie poster tends to promote a movie, provide information, and persuade the audience to watch the movie.